TINGKAT KEPUASAN SEKOLAH MITRA TERHADAP KINERJA MAHASISWA PPL PRODI PENJASKESREK FKIP UNTAN TAHUN AJARAN 2015-2016 - Triansyah, Andika (Universitas Tanjungpura, 2017)
AbstractÂ The purpose of this research was to determine the level of satisfaction the performance of the partner schools force students PPL 2012 Penjaskesrek FKIP Untan. The method used in this research was quantitative descriptive method. Engineering samples used in this study using total sampling so the sample amounted to 53 people. The results of the data analysis related to all aspects of the teacherâ€™s competency showed that the level of satisfaction the performance of the partner schools force students PPL Penjaskesrek FKIP Untan odd semester 2015/2016 is in Good category (B). Meanwhile, from the assessment of competencies prospective teachers required, namely: (1) Social Competence is in the Very Good category; (2) Personality Competence is in the Very Good category; (3) Professional Competence is in the Good category; and (4) Pedagogic Competence is in the Good category.Â Keywords : Level of Satisfaction, Performance, Students PPL